Easter Island Archaeology = Arqueologia En Rapa Nui (Isla De Pascua) ; Homenaje a Daniel Schávelzon a los treinta años del Centro de Arqueología Urbana de la Universidad de Buenos Aires ; A Tribute to Daniel Schávelzon on the 30th anniversary of the Center for Urban Archaeology at the University of Buenos Aires - Schávelzon, Daniel; Silveira, Mario (Access archaeology., 2016)
This well illustrated volume presents in its introduction a personal history of Daniel Schávelzon's experience of Easter Island during his youth before collecting all the papers and work he produced in 2014 leading up to his retirement.